Berjuang Ditengah Kesulitan: Potret Academic Well-being Mahasiswa Difabel di Perguruan Tinggi Inklusif - Prastiwi, Hana Budi; Huwae, Arthur (Kuras Institute, 2025)
Being a student in higher education requires each individual to have the sensitivity to adapt and recognize the scope of lectures independently. The presence of several inclusive universities in Indonesia creates a sense of acceptance, especially for individuals with limitations in carrying out activities, especially lecture activities. It is undeniable that students with disabilities experience difficulties and obstacles and a different dynamic process from non-disabled students. The challenges and obstacles experienced by students with disabilities can affect the decrease in learning motivation so that it leads to learning fatigue both due to the lack of equitable distribution of supporting facilities for students with disabilities and the responsibilities and roles that must be carried out by students with disabilities. The purpose of this research is to find out the portrait of academic well-being of students with disabilities in inclusive universities. This research uses a qualitative approach with a descriptive narrative design. The participants of this study were 3 students with disabilities using snowball sampling technique. Data collection conducted by researchers is using semi-structured interview techniques. The results found that the lack of equitable facilities in inclusive universities is one of the reasons students with disabilities still experience obstacles in undergoing lectures. However, this does not prevent the three participants from continuing to undergo lectures because each individual has positive academic well-being and has social support from the surrounding environment.